Significance of the Lesion–Pleura Relationship in Differentiating Peripheral Inflammatory Lesions and Lung Cancers - Tao Y; Zhang WT; Ding C; Fu BJ; Lv FJ; Chu ZG (Journal of Inflammation Research)
Yang Tao,* Wen-Tao Zhang,* Can Ding, Bin-Jie Fu, Fa-Jin Lv, Zhi-Gang Chu Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fa-Jin Lv; Zhi-Gang Chu, Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, 1# Youyi Road, Yuanjiagang, Yuzhong District, Chongqing, People’s Republic of China, 400016, Tel +86 18723032809, Fax +86 23 68811487, Email cyscitg@hospital.cqmu.edu.cn; chuzg0815@163.comPurpose: To determine the significance of lesion–pleura relationship in differentiating peripheral inflammatory lesions (PILs) and peripheral lung cancers (PLCs).Patients and Methods: From January 2017 to April 2022, a total of 743 patients with 501 PLCs and 292 PILs (≥ 1.5 cm) were retrospectively enrolled. The patients’ clinical characteristics and CT features of lesions in these two groups were analyzed and compared, and the impact of the lesion–pleura relationship (broad or narrow basement and distance between lesion and pleura) on differentiation was specifically assessed.Results: Lesions attached to pleura were more frequent in PILs (188, 64.4%) than in PLCs (244, 48.7%) (P < 0.001), and those with broad basement-to-pleura were also more common in PILs (133, 70.7%) than in PLCs (47, 19.3%) (P < 0.001). Among the 296 lesions with a lesion-pleura distance ≤ 16 mm, the optimal cutoff value of distance was ≤ 8.9 mm (area under curve [AUC], 0.733; sensitivity: 0.770; specificity: 0.623; P < 0.001) for predicting PLCs. Regarding the 728 lesions attached to pleura or with a lesion-pleura distance ≤ 16 mm, the AUC of the model based on the clinical and CT features for predicting PLCs significantly increased from 0.812 to 0.879 after including lesion-pleura relationship (narrow basement or lesion-pleura distance ≤ 8.9 mm) (P < 0.001). Additionally, the lesion–pleura relationship was one of independent indicators for differentiation (odds ratio, 9.433; P < 0.001).Conclusion: When differentiating peripheral lesions (≥ 1.5 cm), it is crucial to consider the basement-to-pleura and lesion-pleura distance besides patients’ clinical characteristics, laboratory parameters and morphological features.Keywords: lung neoplasms, diagnosis, differential, tomography, X-ray computed